Modern european packaging of fresh products - Poluda, Tetyana; Harkusha, Olena O. (My University, 2019)
Nowadays safe and quality packaging is not only a medium for transportation of goods and protection them from mechanical damage, but it is also an important element of the marketing and advertising system, which depends on the demands of consumers. The relevance of the topic is based on the fact that even in today’s busy world people try to keep a healthy lifestyle. So to keep up with the overwhelming pace of life producers invent high-quality packaging that will extend shelf life of products and at the same time will be user-friendly. Therefore, we decided to study the most popular types of packaging.
Keywords: packaging; marketing; user-friendly; маркетинг; зручний; кафедра ділової іноземної мови та міжнародної комунікації